Classificação de barragem de rejeito segundo a categoria de risco e dano potencial associado e análise crítica de passagens da legislação atual de barragens - RAVAGNOLLI, Diana (2022)
The mining sector is a strategic segment of Brazil's economy. However, given that it is based on the exploration of finite resources and its operation generates waste, it is not considered a sustainable activity in its essence. Many mining sites contain tailing dams, and recent accidents resulting from the rupture of these structures have triggered concerns about their safety. This study provides an analysis of the current legal framework that served as the foundation for the Classification of Risk Category (CRI) and the Potential Associated Damage (DPA) of the tailing dam of Territorial São Paulo Mineração Ltda, a mining enterprise that produces stone gravel in the city of São Paulo, SP. This work also presents a critical analises of four excerpts of the legal acts, that lead to two main results: the need to refine the classification regarding CRI and DPA and the urgency of more active participation by Agência Nacional de Mineração - ANM when it comes to the safety of dams. The conclusion of this monograph proposes a future study to readjust the current system of classification of dams in terms of CRI and DPA, with the measurement of the most relevant parameters and attribution of levels of importance that reflect this hierarchy, considering the existence of structures that have distinct characteristics.